Trends in male infertility burden in South Asia: a 30-year analysis of DALYs, prevalence, and future projections based on GBD 2021 - Maqsood, Kaleem; Mehmood, Tahir; Maqbool, Humayoun Huma; Afzal, Ali; Maqbool, Muhammad Faisal; Fatima, Mahnoor; Jan, Tayyba; Ashraf, Samina; Khawar, Muhammad Babar; Muanprasat, Chatchai (Frontiers in Reproductive Health, 2025)
PurposeMale infertility is an increasingly recognized global public health issue. Despite its impact, comprehensive assessments of long-term trends and regional disparities remain limited. Our study focuses on evaluating global and regional trends, particularly in South Asia, in disability-adjusted life years (DALYs) and prevalence of male infertility, and forecasting future patterns.MethodsData from the Global Burden of Disease 2021 were analyzed for the period 1990–2021 to assess trends in DALYs and prevalence. The estimated annual percentage change (EAPC) was used to quantify changes over time. The Autoregression, Integrated, and Moving Average (ARIMA) model was applied to forecast future prevalence and DALYs trends in South Asia.ResultsGlobally, DALYs due to male infertility increased by 17.79% (EAPC 0.51%), and prevalence rose by 16.90% (EAPC 0.50%). South Asia showed a higher burden, with DALYs increasing by 45.66% (EAPC 1.40%) and prevalence by 47.19% (EAPC 1.50%). India showed the greatest rise, with DALYs and prevalence increasing by 55.87% and 58.82%, respectively. The most affected was the 25–29 years age group. A positive association was observed between male infertility burden and sociodemographic index (SDI) values across South Asia. Forecasts predict a continued rise in prevalence, while DALYs may slightly decline by 2030.ConclusionMale infertility is increasing worldwide, with South Asia experiencing the most pronounced burden. While rising trends suggest improved detection, healthcare inequalities persist. Targeted interventions are essential to mitigate the growing impact of male infertility in the region.